Menyulam Harapan dan Kreativitas: Pembelajaran Interaktif untuk Membentuk Anak Panti yang Berkilau - Juwita, Suriani; Triani, Emi; Ritonga, Fajar Utama (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2023)
The implementation of Field Work Practice 2 (PKL) is an integral part of the Social Welfare Science curriculum, serving as a mandatory step in preparing students to become social workers. The Interactive Learning Method is an approach in the teaching process that actively involves children throughout the learning process. Interactive learning for children, particularly in orphanages, can be implemented by considering their unique characteristics and needs. Interactive learning not only focuses on academic improvement but also on the development of social skills, creativity, and problem-solving abilities. In the interactive learning activities at Sendoro Orphanage, the stages used are the General Method: Engagement, Intake & Contract, Assessment, Planning, Intervention, Evaluation, and Termination. Several interactive activities conducted to support learning in the orphanage include skill workshops, interactive storytelling, educational games, simple experiments, collaborative art activities, interactive quizzes, group sports, small performances, and group discussions. The final outcome of the interactive learning program in the orphanage has been positive, enhancing children's engagement, learning abilities, and strengthening their social skills. In this context, evaluating the academic progress and personal development of the children is essential to measure the effectiveness of the program.